2018
DOI: 10.5152/eurasianjmed.2018.17269
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Concurrent Partial Anomalous Pulmonary Venous Return and Lung Cancer of the Same Lobe

Abstract: Partial anomalous pulmonary venous return (PAPVR) is a rare congenital left-to-right shunt where pulmonary veins drain into systemic circulation. This is a presentation of the case of a patient with concurrent PAPVR and adenocarcinoma of the same lobe. The pulmonary veins of right upper lobe drained into superior vena cava (SVC), whereas the middle and lower lobes veins drained into the left atrium as two distinct vessels. Surgeons should always perform a diligent search for anomalous vascular structure using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There have also been described cases in which the PAPVR presented on the left but the intended resection on the right, leading to increased shunt flow and subsequent right heart failure [ 4 ]. Roughly 80–90% of cases of PAPVR have an associated ASD [ 2 , 11 ]. Special care should be given to this relationship as this could affect surgical management [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been described cases in which the PAPVR presented on the left but the intended resection on the right, leading to increased shunt flow and subsequent right heart failure [ 4 ]. Roughly 80–90% of cases of PAPVR have an associated ASD [ 2 , 11 ]. Special care should be given to this relationship as this could affect surgical management [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, this condition afflicts adults by presenting with the left superior pulmonary vein draining to the innominate vein or the right superior pulmonary vein draining to the superior vena cava. Often times, PAPVR presents with a concurrent atrial septal defect (ASD) found in up to 80% of patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%